Labeless AC impedimetric antibody-based sensors with pg ml-1 sensitivities for point-of-care biomedical applications. - Barton, Andrew C.; Collyer, Stuart D.; Davis, Frank; Garifallou, Goulielmos-Zois; Tsekenis, Georgios; Tully, Elizabeth; O'Kennedy, Richard; Gibson, Tim; Millner, Paul A.; Higson, Seamus P. J. (Elsevier Science B.V., Amsterdam., 2009)
This paper describes the development and characterisation of labeless immunosensors for (a) the cardiac drug digoxin and (b) bovine serum albumin (BSA). Commercial screen-printed carbon electrodes were used as the basis for the sensors. Two methods were used to immobilise antibodies at the electrode surface. Aniline was electropolymerised onto these electrodes to form a thin planar film of conductive polyaniline; the polyaniline film was then utilised as a substrate to immobilise biotinylated anti-digoxin using a classical avidin- biotin affinity approach. As an alternative approach, poly(1,2-diaminobenzene) was electrodeposited onto the carbon electrodes and this modified surface was then sonochemically ablated to form an array of micropores. A second electropolymerisation step was then used to co-deposit conductive polyaniline along with antibodies for BSA within these pores to produce a microarray of polyaniline protrusions with diameters of several μm, containing entrapped anti- BSA
Keywords: AC impedance; Immunosensor; Polyaniline; Microelectrode; BSA; Digoxin